KHOJA AHRAR VALI ON PERCEPTION OF IDENTITY: A COMPARATIVE-PHILOSOPHICAL ANALYSIS (Scientific journal of the Fergana State University, 2024)
The article philosophically analyzes the ideas of Khoja Akhror Vali, Jalaluddin Rumi, Alisher Navoi regarding self-awareness, which is a pressing issue in human philosophy